Pelatihan Penggunaan Media Pembelajaran Berbantuan Laptop dan Handphone di MTs Al Muhajirin Ambon - Wa Ima; Aminah Rehalat; Jenny K. Matitaputty; Tama Maysuri; Reihana Kapitanhitu (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service activity is carried out as a response to the needs of teachers at MTs Al Muhajirin Ambon in enhancing their ability to utilize technology-based learning media, particularly laptops and mobile phones. In this digital era, mastery of digital learning devices and applications has become very important for creating an engaging, interactive, and relevant learning process for today's students. However, initial observations indicate that most teachers still face challenges in using technology due to limitations in training and support. Therefore, this activity is designed in the form of an integrated training program that includes the introduction, practice, and evaluation of various digital learning media and applications such as PowerPoint, Capcut, Canva, and smartphone-based and laptop applications. The training was conducted participatively through interactive lectures, demonstrations of tools and applications, hands-on practice, discussions and Q&A, as well as evaluation and reflection. The results of this activity showed a significant increase in teachers' understanding and skills, as well as a growing motivation to integrate technology into learning. This activity is expected to be the beginning of digital transformation in the madrasah environment and to support the improvement of education quality in the wider Ambon area.